Hydrogels based on methylated-alginates as a platform to investigate the effect of material properties on cell activity. The role of material compliance. (1st July 2023) - Scognamiglio, Francesca; Cok, Michela; Piazza, Francesco; Marsich, Eleonora; Pacor, Sabrina; Aarstad, Olav A.; Aachmann, Finn L.; Donati, Ivan
Abstract: Alginate-based hydrogels with tunable mechanical properties are developed by chemical methylation of the polysaccharide backbone, which was performed either in homogeneous phase (in solution) or in heterogeneous phase (on hydrogels). Nuclear Magnetic Resonance (NMR) and Size Exclusion Chromatography (SEC-MALS) analyses of methylated alginates allow to identify the presence and location of methyl groups on the polysaccharide, and to investigate the influence of methylation on the stiffness of the polymer chains. The methylated polysaccharides are employed for the manufacturing of calcium-reticulated hydrogels for cell growth in 3D. The rheological characterization shows that the shear modulus of hydrogels is dependent on the amount of cross-linker used. Methylated alginates represent a platform to explore the effect of mechanical properties on cell activity. As an example, the effect of compliance is investigated using hydrogels displaying similar shear modulus. An osteosarcoma cell line (MG-63) was encapsulated in the alginate hydrogels and the effect of material compliance on cell proliferation and localization of YAP/TAZ protein complex is investigated by flow cytometry and immunohistochemistry, respectively. The results point out that an increase of material compliance leads to an increase of the proliferative rate of cells and correlates with the translocation of YAP/TAZ inside the cell nucleus.